Multiscale Modeling Indicates That Temperature Dependent [Ca2+]i Spiking in Astrocytes Is Quantitatively Consistent with Modulated SERCA Activity - Niko Komin; Mahsa Moein; Mark H. Ellisman; Alexander Skupin (Neural Plasticity)
Changes in the cytosolic Ca2+ concentration ([Ca2+]i) are the most predominant active signaling mechanism in astrocytes that can modulate neuronal activity and is assumed to influence neuronal plasticity. Although Ca2+ signaling in astrocytes has been intensively studied in the past, our understanding of the signaling mechanism and its impact on tissue level is still incomplete. Here we revisit our previously published data on the strong temperature dependence of Ca2+ signals in both cultured primary astrocytes and astrocytes in acute brain slices of mice. We apply multiscale modeling to test the hypothesis that the temperature dependent [Ca2+]i spiking is mainly caused by the increased activity of the sarcoendoplasmic reticulum ATPases (SERCAs) that remove Ca2+ from the cytosol into the endoplasmic reticulum. Quantitative comparison of experimental data with multiscale simulations supports the SERCA activity hypothesis. Further analysis of multiscale modeling and traditional rate equations indicates that the experimental observations are a spatial phenomenon where increasing pump strength leads to a decoupling of Ca2+ release sites and subsequently to vanishing [Ca2+]i spikes.